improving performance of laying hens - A.P Sinurat; P Ketaren; A.J Cowieson; M.H.L Bento (Jurnal Ilmu Ternak dan Veteriner, 2012)
A trial was conducted in order to study the effect of the supplementation of Avizyme 1500® (Danisco Animal Nutrition, Marlborough, UK) on the performance of laying hens for one year. A control diet based on corn – soybean meal was formulated to meet nutrient requirement of ISA Brown laying hens. Two treatments, the control diet (C) and C + 1000 g Avizyme/tonne diet were tested. Each diet was fed to 80 birds (20 replicates of 4 birds) from 20 to 72 weeks of age, and performances of birds (feed intake, egg production, egg size, egg mass, feed conversion ratio, and egg quality) were measured. All data were subject to analyses of variance following the t-test. Results showed that the addition of Avizyme 1500 to the feed reduced feed intake by 4% (P < 0.01), mortality by 75 % or from 15% to 3.75% (P < 0.01) and improved the feed conversion ratio by 3 % (P < 0.05).  The high mortality of the control treatment (15%) is explained by an E.coli infection that was observed following the post-mortem examination of dead birds. The egg production (HD and HH), egg size and egg mass however were not significantly affected by the Avizyme supplementation. Egg quality (HU, yolk colour score, yolk weight and shell thickness) was not significantly affected by Avizyme supplementation. It can be concluded that the supplementation of 1000 g Avizyme /tonne of diet improved feed efficiency and this was mediated via a reduction in feed intake. Key Words: Egg Production, Enzyme, Feed Convertion Ratio, Egg Quality